PERAN MANAJEMEN STRATEGI BAGI PERUSAHAAN DALAM MENGHADAPI PERSAINGAN GLOBAL PADA ERA REVOLUSI INDUSTRI 4.0 DAN SOCIETY 5.0: Digitalization; Global Competitiveness; Industrial Revolution 4.0, Society 5.0; Strategic Management - Rahman Efandi; Sarmini; Sri Yanti; Ngaliman (Universitas Batam, 2026)
Having a solid and long-lasting position in the market is the primary goal of strategic management of a business. In the period of the Industrial Revolution 4.0 and Society 5.0, this study attempts to investigate the function of strategic management in dealing with global competitiveness. Companies use strategic management as a framework to develop, carry out, and assess policies in order to gain a competitive edge. Companies can become more competitive by implementing strategic management, particularly in the digital age, which is full of opportunities and problems. In the face of technology's rapid advancement, businesses can establish long-lasting competitive advantages by effectively leveraging digital innovation, big data, and artificial intelligence (AI). According to the study's findings and conclusions, businesses need to be prepared to handle a variety of issues, including data management, cyber security, and shifting business models brought on by digitalization. Additionally, it's critical for businesses to keep improving the digital abilities of their staff members so they can adapt to change and innovate to produce better goods and services. In the age of the Industrial Revolution 4.0 and 5.0 Societies, strategic management can guarantee that businesses stay relevant and competitive by taking a flexible, data- driven and responsive approach to market developments.